Investigating in vitro bioactivity, magnetic and mechanical properties of iron and cobalt oxide reinforced (45S5-HA) biocomposite - Prasad S.; Vyas V.K.; Harijan P.K.; Ershad M.; Pyare R. (My University, 2025)
Bioactive glass-based composite (45S5–HA–Fe2O3–CoO) were prepared through controlled crystallization of respective biocomposites through sintering process. The crystalline phases in bioactive glass composites were identified by using X-ray diffraction (XRD) analysis. Nucleation and crystal growth temperatures were found by thermogravimetric analysis (TGA)/differential thermal analysis (DTA) technique. These biocomposite were immersed in simulated body fluid (SBF) for different time periods, i.e. 1, 3, 7, 14 and 21 days. Hydroxyapatite was formed on these samples and was confirmed by FTIR, SEM, and pH measurements. The magnetic properties of these samples were evaluated by vibrating sample magnetometer (VSM).The density and compressive strength were enhanced with an increase in Fe2O3 and CoO content in the base bioglass powder. This study will help the researcher to know the bioactivity and magnetic properties of the implant material like bone and teeth. © 2017, Australian Ceramic Society.